Model Catalytic Studies of Liquid Organic Hydrogen Carriers: Indole/Indoline/Octahydroindole on Ni(111) - Steinhauer, Johann; Bachmann, Philipp; Freiberger, Marie; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2020)
N-heterocycles belong to the class of so-called liquid organic hydrogen carriers (LOHCs), which have been identified as suitable materials for chemical hydrogen storage due to favorable hydrogen storage capacity and reaction kinetics. In this contribution, we focus on the dehydrogenation reaction of hydrogen-rich octahydroindole, its dehydrogenation intermediate indoline, and hydrogen-lean indole. Octahydroindole has a hydrogen storage capacity of 6.4 wt %, and indoline has 1.7 wt %. We investigated the mechanism of the temperature-induced dehydrogenation of the three compounds after adsorption on Ni(111) at low temperatures. Nickel is attractive as an effective and low-priced dehydrogenation catalyst, which potentially could replace more expensive Pt and Pd in industrial applications. We compare the obtained results with our previous work on Pt(111) for the same LOHC system and for N-ethylcarbazole/H-12-N-ethylcarbazole. A comprehensive understanding of the reaction mechanism was obtained by combining high-resolution X-ray photoelectron spectroscopy with temperature-programmed desorption lab experiments. For all three compounds, we find dehydrogenation at the nitrogen atom above 270 K (indole, >= 130 K; indoline, >240 K; octahydroindole, >270 K). For indoline and octahydroindole, we observe simultaneous dehydrogenation at the carbon atoms, resulting in an indolide surface species. For octahydroindole, small amounts of side products and decomposition products are observed throughout the reaction pathway. Above 380 K, the indolide species decomposes into fragments for all three compounds.
CRIS-Team WoS Importer:2020-11-27